Implementasi Kebijakan Pembentukan Balai Kesehatan Olahraga Masyarakat Provinsi Sulawesi Utara - Pangalila, Sjelvie F.; Areros, William Agustinus; Londa, Very Y. (JURNAL ILMIAH SOCIETY, 2015)
Society Sports Health Center North Sulawesi province is one of the Regional Technical Implementation Unit of North Sulawesi Provincial Health Office as one of the health care facility has a strategic role in the effort to accelerate the improvement of health, the people of Indonesia. Using qualitative methods, this study aims to reveal and analyze the implementation of policy formation Society Sports Health Center of North Sulawesi Province.This study concluded the implementation of policy formation Society Sports Health Center of North Sulawesi province has not run in an effort to create a society that is healthy, fit, quality, productive and competitive through sport. does socialization through the use of communication media, adding that employees have an educational background as a health care professional sports, Putting the hall in a more strategic location, make improvements by adding equipment and operational funds, outlining the duties and functions based on a clear organizational structure, to make improvements the structure organsiasi with more technical focus on public health services and undertake the preparation of a Standard Operating Procedural guidelines and sports health care.Keywords: Implementation, Sports Health Center, Community.